Tet inactivation disrupts YY1 binding and long-range chromatin interactions during embryonic heart development - Shaohai Fang (Nature Portfolio, 2019)
Tet-mediated DNA demethylation is intimately involved in reguatling embryonic development. Here the authors characterise DNA methylation and hydroxymethylation dynamics during early cardiac development in both human and mice and provide evidence that Tet-mediated DNA demethylation plays a role in regulating chromatin organization during early heart development.